TYPES OF CHILDREN POEM IN DIVAN AL-ATFAL BY SULAIMAN AL-ISA - Roshanfekr, Akram; Askari, Sadegh; Akbarpour, Somayeh (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2017)
Children poem is a literary type which has the potential to be versified with other different types. Children poet is aware of child’s interests and mood and sometimes by using easy words and fluent phrases and proportionate to the notion tries to help the child in learning and expanding his vocabulary domain with new words. In this way, poem verses are versified with the aim of teaching notions and categorized under didactic poetry type. Sulaiman al-Issa from Syria is considered among the founders of children poem in Arabic literature. He has a Divan entitled ‘Divan al-Atfal’. The present study with a descriptive-analytic approach attempts to review it with the aim of determining the applied types in his poems. The most important result of the article is the presence of nature poem, didactic poem, and social and entertainment poetry types in Divan al-Atfal.